Effect of blast-related mTBI on the working memory system: a resting state fMRI study. - Pagulayan, Kathleen F.; Petrie, Eric C.; Cook, David G.; Hendrickson, Rebecca C.; Rau, Holly; Reilly, Melissa; Mayer, Cindy; Meabon, James S.; Raskind, Murray A.; Peskind, Elaine R.; Kleinhans, Natalia (Brain Imaging & Behavior, 2020)
Reduced working memory is frequently reported by Veterans with a history of blast-related mild traumatic brain injury (mTBI), but can be difficult to quantify on neuropsychological measures. This study aimed to improve our understanding of the impact of blast-related mTBI on the working memory system by using resting state functional magnetic resonance imaging (fMRI) to explore differences in functional connectivity between OEF/OIF/OND Veterans with and without a history of mTBI. Participants were twenty-four Veterans with a history of blast-related mTBI and 17 Veterans who were deployed but had no lifetime history of TBI. Working memory ability was evaluated with the Auditory Consonants Trigrams (ACT) task. Resting state fMRI was used to evaluate intrinsic functional connectivity from frontal seed regions that are known components of the working memory network. No significant group differences were found on the ACT, but the imaging analyses revealed widespread hyper-connectivity from the frontal seed regions in the Veterans with a history of mTBI relative to the deployed control group. Further, within the mTBI group, but not the control group, better performance on the ACT was associated with increased functional connectivity to multiple brain regions, including cerebellar components of the working memory network. These results were present after controlling for age, PTSD symptoms, and estimated premorbid IQ, and suggest that long-term alterations in the functional connectivity of the working memory network following blast-related mTBI may reflect a compensatory change that contributes to intact performance on an objective measure of working memory.